Fertility Outcomes and Sperm-DNA Parameters in Metastatic Melanoma Survivors Receiving Vemurafenib or Dabrafenib Therapy: Case Report - Ghezzi, Marco; Garolla, Andrea; Magagna, Sabina; Šabovich, Iva; Berretta, Massimiliano; Foresta, Carlo; De Toni, Luca (Frontiers in Oncology, 2020)
Melanoma is a frequent neoplasm in young adult males in reproductive age, 10% of them degenerating into regional and/or distant metastases (MM). The use of BRAF inhibitors (BRAFi) vemurafenib and dabrafenib is effective in MM patients harbouring BRAF V600E/K/D mutations. Despite the increased life expectancy in MM patients treated with BRAFi, concerns are raised by the possible side effects and increased risk of gonado- and/or genotoxicity associated with these drugs. However, these aspects are currently under-investigated. Here we report the different fertility outcome in two cases of MM patients, harbouring BRAF V600E mutation, that received vemurafenib and dabrafenib respectively. The first patient, 36 years at recruitment in 2015 and seeking fatherhood, had an history of relapsing melanoma since 2002 and undergone to numerous interventions and chemotherapy cycles. In November 2011, following detection of BRAF V600E mutation, a daily treatment with vemurafenib (1440 mg) was prescribed with preventive gamete cryopreservation. BRAFi was effective in the clinical stabilization of the disease. In 2015, semen evaluation at follow-up showed sperm parameters within the normal range and no signs of alteration of either sperm function or sperm-DNA. On these bases, no contraindications for fatherhood were given. After a month of free intercourses, the 38-year-old partner achieved spontaneous pregnancy with a regular course, normal male fetal karyotype and a full term birth. The second patient, 39 years at recruitment in 2018 and seeking fatherhood, had an history of melanoma since 2012. In 2018, following the evidence of disease relapse and detection of the BRAF V600E mutation, treatment with dabrafenib/trametinib (300 mg/day/2 mg/day) was initiated together with preventive gamete cryopreservation. In 2019, semen evaluation at follow up showed sperm count and motility below the reference values, associated with increased indexes of sperm aneuploidies and sperm DNA fragmentation. Accordingly, access to assisted reproduction technique with cryopreserved spermatozoa was suggested. Differently from dabrafenib that was associated to damage to spermatogenesis, high-dose vemurafenib showed no association with gonadotoxicity and genotoxicity in humans, even at high doses. Although further confirmation are required, our data represent a valued cue in oncofertility counseling to MM patients in addition to preventive cryopreservation.